The role of sour and bitter perception in liking, familiarity and choice for phenol-rich plant-based foods. (October 2021) - Pagliarini, E.; Proserpio, C.; Spinelli, S.; Lavelli, V.; Laureati, M.; Arena, E.; Di Monaco, R.; Menghi, L.; Gallina Toschi, T.; Braghieri, A.; Torri, L.; Monteleone, E.; et al.
Highlights: Sour and bitter perception is positively correlated both in water and in model foods. Sour and bitter perception decrease with age especially at higher taste intensity. Responsiveness to sour and bitter is related to liking for plant-based food. Food choice for phenol rich plant-based food tend to be associated with taste perception. Abstract: Among factors influencing food preferences and choices, individual differences in taste perception play a key role in defining eating behaviour. In particular, sour and bitter responsiveness could be associated with the acceptance and the consumption of phenol-rich plant-based foods recommended for a healthy diet. The aim of this study was to investigate, in a large population sample, the associations among sour and bitter responsiveness and liking, familiarity and choice for plant-based foods characterized by these target tastes. Adults aged 18 to 60 years (n = 1198; 58% women) were tested for their sour and bitter responsiveness both in water solutions and in food models (pear juice-based beverages modified in citric acid content to induce different levels of sourness: 0.5, 2.0, 4.0 and 8.0 g/kg; chocolate pudding samples modified in sucrose content to induce different levels of bitterness: 38, 83, 119, 233 g/kg). Familiarity, stated liking and choice for fruit juices and vegetables varying for sour/bitter taste (high in bitter/sour taste: e.g. grapefruit juice and cauliflower; low in bitter/sour taste: e.g. zucchini and pineapple juice) were measured. Results showed a significant positive correlation between bitter and sour taste perception in water solutions and model foods, as well as a positive correlation between the perceived intensity of the two taste stimuli. Subjects characterized by high responsiveness to the two target stimuli were found to give lower liking scores to foods characterized by sour/bitter tastes and tended to choose less sour/bitter foods compared to less responsive subjects. Thus, food choice for phenol rich plant-based products could be associated with a reduced responsiveness to bitter and sour tastes and a consequent higher acceptance of food products characterized by these taste qualities.